2022
DOI: 10.1146/annurev-phyto-021621-115027
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care DNA Amplification for Disease Diagnosis and Management

Abstract: Early detection of pests and pathogens is of paramount importance in reducing agricultural losses. One approach to early detection is point-of-care (POC) diagnostics, which can provide early warning and therefore allow fast deployment of preventive measures to slow down the establishment of crop diseases. Among the available diagnostic technologies, nucleic acid amplification–based diagnostics provide the highest sensitivity and specificity, and those technologies that forego the requirement for thermocycling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 136 publications
0
17
0
Order By: Relevance
“…Previous work by our group and others have established that reducing betaine concentration in the reaction mix can significantly decrease the amplification time of the target DNA ( Zou et al., 2020 ), hence a concentration of 0.5M betaine was used in the initial Lxx LAMP assays. One of the drawbacks of isothermal LAMP amplification is its propensity to produce non-specific amplification products due to primer dimerization in the absence of DNA template ( Botella, 2022 ). Our experiments revealed that the use of 0.5M betaine occasionally produced self-amplification in no-template controls (NTCs) resulting in the production of false positives ( Supplementary Figure 3 ), therefore we performed a betaine concentration titration experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by our group and others have established that reducing betaine concentration in the reaction mix can significantly decrease the amplification time of the target DNA ( Zou et al., 2020 ), hence a concentration of 0.5M betaine was used in the initial Lxx LAMP assays. One of the drawbacks of isothermal LAMP amplification is its propensity to produce non-specific amplification products due to primer dimerization in the absence of DNA template ( Botella, 2022 ). Our experiments revealed that the use of 0.5M betaine occasionally produced self-amplification in no-template controls (NTCs) resulting in the production of false positives ( Supplementary Figure 3 ), therefore we performed a betaine concentration titration experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Unless stated, LAMP reaction mixture contained 0.8M betaine, 20mM Tris-HCl (pH 8.8), 50mM KCl, 10mM (NH 4 ) 2 SO 4 , 0.1% Tween ® 20, 8mM MgSO 4 , 1.2mM dNTP (each), 0.32 U/mL Bst 2.0 warm start polymerase (New England Biolab), 0.2μM (each) F3 and B3 primers, 0.8μM (each) loop forward and reverse primer, 45 μL of reactions were incubated at 65°C for 60 minutes in our custom made hand held diagnostic device ( Botella, 2022 ). When necessary, the amplified products were visualized using agarose gel electrophoresis, the raw values and real time curves were analyzed using Microsoft Excel.…”
Section: Methodsmentioning
confidence: 99%
“…Recent advanced methods in NAATs are based on isothermal amplification (IA), which overcomes the need for thermal cycling given the ability to amplify the sequence of interest at constant temperatures. , By eliminating the need for thermocyclers, amplification techniques are set free from energy-demanding and technologically complex systems, opening the door to POCT and in-field applications. IA techniques are thus suitable for laboratories lacking expensive PCR equipment and for low-resource settings. In addition, IA methods require less sample and reagent preparation, and the results can be read through different approaches (e.g., turbidimetry, LF), enhancing their accessibility and ease-of-use. ,, …”
Section: Nucleic Acid Amplification Techniquesmentioning
confidence: 99%
“…[ 8 ] NAATs are also important for other targets including liquid biopsies for cancers, [ 9 ] sexually transmitted infections (STIs), [ 10 ] vector‐borne diseases, [ 11 ] drug resistance in pathogens, [ 12 ] environmental DNA for surveillance of invasive species, [ 13 ] and early detection of agricultural pests and pathogens. [ 14,15 ]…”
Section: Introductionmentioning
confidence: 99%